THE ROLE OF INDONESIAN NATIONAL LIBRARY IN PRESERVING AND DISSEMINATING MANUSCRIPTS - Alfida, Alfida (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
Indonesian National Library has preserved Indonesian manuscripts by collecting and digitizing manuscripts in some areas of Indonesia, such as Yogyakarta, East Sumatera, Cirebon, and Pulau Penyengat. However, a lot of work should be done compared with the number of manuscripts in Indonesia.  Ironically, the same thing does not happen with national library. Disseminating is even worse. The library has provided online catalog for the manuscripts. However, the entry of online catalog is lesser than the printed ones, and the electronic file is always not there. This paper duscusses on; firstly, manuscripts in Indonesia; Secondly, the intended role of the national library in preserving and disseminating the manuscripts; thirdly, the problematic aspect of the collection itself and the state of the manuscripts and above all, the unfulfilled manuscripts offers for researching purpose; fourthly, possibility to collaborate to have a portal or virtual manuscripts on Southeast Asia in a regional setting.